The Influence of Leadership, Organizational Culture and Dicipline on the Performance of Village Officials in Cempa District Pinrang Regerency - Nurhikmah, Nurhikmah; Jam’an, Andi; Ahmad, Ahmad (Journal of Public Representative and Society Provision, 2025)
The performance of village apparatus is a crucial determinant of public service quality and community trust at the local level of governance. However, in Cempa District, Pinrang Regency, several challenges remain evident, including limited responsiveness, lack of innovation in public services, and weak adherence to established service standards. Addressing these challenges requires a deeper understanding of organizational and behavioral factors that shape apparatus performance. This study aims to analyze the influence of leadership, organizational culture, and discipline on the performance of village officials. Employing a quantitative survey design, data were collected from 42 respondents representing all village apparatus across seven villages in Cempa District through a structured questionnaire. The data were tested for validity and reliability and analyzed using multiple linear regression with SPSS. The results demonstrate that leadership, organizational culture, and discipline each exert a positive and significant effect on performance, with organizational culture emerging as the most influential factor. These findings suggest that strengthening leadership accountability, cultivating a supportive organizational culture, and enforcing consistent discipline are key strategies to improve the effectiveness and professionalism of village governance. The study contributes to the growing body of literature on public sector performance and provides practical recommendations for policymakers and local governments in fostering sustainable development at the village level.